VERBA TAKTRASITIF BERPELENGKAP DALAM BAHASA MELAYU JAMBI SUATU KAJIAN SINTAKSIS - Rustam Rustam (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2014)
The predicate of intrasitive complement verb in Jambi Malay language clause or sentence can be described as follows: (1) compulsory intrasitive complement verb like basic verb and affix verb be-/-kan + (1) rediplication verb by using pattern SPCom, SadcPCom, and AdcPcom. Constituen of posverb catagorize nominal (1), adjectiva (1), adverbia(1), and numeralia(I). And (2) arbitrary intransitve complement verb like elementary verb and affiz verb be-/an + nominal(I) by using pattern SPCom. Constituent of posverba have verba(I), adjectiva(I), numeralia(I), and adverbia(I) categories. Keywords : Intransitive complement verb, Jambi Malay Language.